The Magic of Writing - Johanna Stöttinger 1994- (2017)
This paper, written as an English Creative Writing thesis, is the result of a lifelong fascination for the English language, for dragons and magic, and a course in creative writing by Dr. Anna Heiða Pálsdóttir that I attended during my exchange year at the University of Iceland in the spring of 2015. The first part is a novella called The Legend of Quaronaax: A Mage’s Tale of around 19,000 words and the second part is an exposition, The Magic of Writing of around 3,700 words. The Legend of Quaronaax tells the tale of a prodigious young mage called Quaronaax who is indentured at the master magician’s tower in the Ashlands. Forty years have passed since the mountain Tol Hrokkronaax erupted and wiped out the young mage’s people. It has been a time of peace. With the discovery of the returned abundant growth of the Ashland fungi and Quaronaax sensing a strange and dark magic in the atmosphere of the mountain and the Ashlands, the world is in peril once more. Quaronaax seems to be the only one who can feel the dark magic. He and his friend decide to secretly investigate by themselves. With the help of the legendary Lady of the Dreki, descendant of ancient dragons, he begins to understand the implications of the shifting magic and embarks on a journey to seek out the evil under the mountain and defeat it once and for all. The Magic of Writing describes in great detail what inspired the main themes and magical elements of the story, how I became more confident with point of view, how I conceived the plot and made it round and coherent, how my characters have been created, and how the fact that English is not my first language has affected the writing process.